2005
DOI: 10.1152/ajprenal.00353.2004
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene relaxes rat intrarenal arteries by inhibiting Ca2+ influx

Abstract: Raloxifene may confer vascular benefits without causing estrogen-related side effects. However, its action on renal vascular circulation is unknown. This study aimed to examine the sex difference and roles of the endothelium and Ca 2ϩ channels in rat renovascular relaxation to raloxifene. On isolated intralobar renal artery rings mounted in a myograph and contracted by U-46619, concentration-relaxation curves were constructed for raloxifene and contractions to CaCl 2 were studied. Changes in intracellular Ca 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…This reduced sensitivity to E 2 in larger arteries is in agreement with findings of others (Lindsey et al 2011). Furthermore, the differential sensitivities to E 2 of the mesenteric, renal, and uterine arteries observed in this study are similar to values reported by others (Naderali et al 1999, Leung et al 2005, Scott et al 2007 Previous studies have shown that in vivo administration of the nonselective ER antagonist ICI 182 780 into one uterine artery of ovariectomized and E 2 -treated nonpregnant sheep blunted the E 2 effect on uterine blood flow, confirming its ER dependence (Magness et al 2005). Here, we show that ICI 182 780 resulted in a significant rightward shift in the CRCs to E 4 and E 2 , suggesting the contribution of ER.…”
Section: Discussionsupporting
confidence: 93%
“…This reduced sensitivity to E 2 in larger arteries is in agreement with findings of others (Lindsey et al 2011). Furthermore, the differential sensitivities to E 2 of the mesenteric, renal, and uterine arteries observed in this study are similar to values reported by others (Naderali et al 1999, Leung et al 2005, Scott et al 2007 Previous studies have shown that in vivo administration of the nonselective ER antagonist ICI 182 780 into one uterine artery of ovariectomized and E 2 -treated nonpregnant sheep blunted the E 2 effect on uterine blood flow, confirming its ER dependence (Magness et al 2005). Here, we show that ICI 182 780 resulted in a significant rightward shift in the CRCs to E 4 and E 2 , suggesting the contribution of ER.…”
Section: Discussionsupporting
confidence: 93%
“…Vasoreactivity of the interlobar renal arteries were measured as described (27). The effects of various compounds on EDRs and EDCs were tested.…”
Section: Vascular Reactivitymentioning
confidence: 99%
“…Arteries were prepared and changes of isometric tension were recorded23. The organ chamber was filled with 5 ml Krebs solution and gassed by 95% O 2 -5% CO 2 at 37 °C (pH ~7.4).…”
Section: Methodsmentioning
confidence: 99%